Penguatan Digitalisasi Pembelajaran Bagi Guru dan Siswa di Sekolah Menengah Kejuruan berbasis Higher Order Thinking Skill (HOTS) - Rahmaniar Rahmaniar; Sri Wahyuni; Eko Hariyanto (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2023)
Background: Strengthening the digitization of learning in the Kegiatan Kemandirian Masyarakat (KKM) program was carried out for teachers and students at SMKS Imelda Medan. Activities with teachers, namely training in the field of design principles as well as competency test assessments by supporting partners of the digital technology Professional Certification Institute (LSP), while student activities are carried out training in making simulations based on power simulation software. Implementation activities aim to train 4C competencies. The 4C competencies are creative thinking skills, critical thinking, communication, and collaboration for teachers and students. Methods: The implementation method is carried out by training and direct assistance to SMKS Imelda partners as well as teacher competency tests in the computer laboratory, covering the areas of training in the principles of design and communication. The indicators measure measurable activities by interviewing and distributing questionnaires to training participants, as well as inviting participants to BNSP to obtain competency certification in the design field. Results: 20 teachers obtained good results in training and have been proposed to obtain expertise certification, while for students, the software used has been assessed as practical by SMK students at 0.837 points in the good category. From the results of the activity, it can be interpreted that design assistance training for teachers and simulations for students have an impact on the implementation of critical thinking skills in realizing the ability of teachers and students to make designs and simulations with the help of software, as indicated by the results of the KKM program.